Fibroblastic osteosarcoma in a guinea pig (Cavia porcellus) - Vetter, Joerg Richard; Maidana, Leila Gertrudis; Gonzalez-Vatteone, Roger; Brítez-Valinotti, César Esteban; Ramírez-Diarte, Raquel (Brazilian Journal of Veterinary Pathology, 2023)
The article describes the case of a 3 year 6 months old Guinea Pig (Cavia porcellus) that was assisted at the Wildlife and Exotic Animal Practice of the Faculty of Veterinary Sciences, National University of Asunción. The patient presented a hard mass in the right hind limb extending from the proximal portion of the femur, projecting caudally to the proximal tuberosity of the calcaneus, with an increase in temperature, and a marked increase in sensitivity. Radiographic diagnosis refers to a mass with amorphous areas of mineral density. Fine needle aspiration puncture revealed an undifferentiated malignant proliferative process, requiring histopathological analysis to characterize the process. Disarticulation was performed and subsequent histopathologic diagnosis under hematoxylin-eosin and Masson’s trichrome stain revealed fibroblastic osteosarcoma.